Pengaruh Reward dan Punishment Terhadap Disiplin Kerja Melalui Motivasi Kerja sebagai Variabel Intervening : Studi pada Pegawai Kantor Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Lombok Tengah - Baiq Nurmaulida Nindiyana; Djoko Suprayetno; I Nyoman Nugraha (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is entitled the effect of Reward and Punishment on Work Discipline Through Work Motivation as an Intervening Variable (Study on Employees of the Central Lombok Regency Community and Village Empowerment Office). This research aim to determine the effect and significance of reward and punishment variables on work discipline through work motivation as an intervening variable. The number of repondents in this study were 33 people from the Central Lombook Regency Community and Village Empowerment Office employees and this study used quantitative research methods. The data analysis used is path analysis, as well as statistical test namely the F test, T test, and R Square test processed using IBM SPSS 20. The result of this research indicate that : 1) Reward has no significant effect on work discipline, 2). Punishment has a significant effect on work discipline, 3). Work Motivation has a significant effect on work discipline, 4). Reward has no significant effect on work motivation, 5). Punishment has no significant effect on work motivation, 6). Reward has no significant effect on work discipline through work motivation, 7). Punishment has no significant effect on work discipline through work motivation.